HERITAGE OF INDUSTRIAL ARCHITECTURE IN NOWADAYS’ CULTURAL ENVIRONMENT - Brokāne, Natālija; Strode, Aina (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2018)
The aim of the article is to study the concept of industrial heritage and its examples, trends in the usage of old factory buildings, to carry out theoretical analysis of industrial tourism, to evaluate the possibilities of industrial tourism in Latvia and Rezekne, by performing a survey of residents of the city.In the modern world a large number of factories and objects of industrial heritage cannot exist for their primary purpose anymore: they are demolished to clear the territory for new buildings, they are reconstructed, rebuilt, transforming the factories for various needs and purposes. Their applications nowadays are very diverse, ranging from art galleries to hotels and technical parks. This is a solution to many problems related to old factories and their territories. Transforming factory buildings and territories creates opportunities for industrial tourism, which in turn promotes regional development, provides new job opportunities in the city, and develops economy.